Revision of the genus Metura (Lepidoptera: Psychidae) with description of two new species - Beaver, Ethan P. (Zootaxa, 2020)
The genus Metura Walker, 1855 is revised, with all species figured, diagnosed, and redescribed. Two new species are described from Australia: Metura phyllosacca sp. n. from south eastern Queensland and north-eastern New South Wales, and M. falcata sp. n. from Lord Howe Island. The species Oiketicus aristocosma Lower, 1908 is here recognised as Metura aristocosma (Lower, 1908) comb. n. The mature larval bags, diagnostic by way of their structure, are figured for all species. A key is provided for the adult males and larval bags of this genus. A brief discussion is included, outlining potential research directions.